Structural and thermal diffusivity studies of polycrystalline (CuSe)1-xSex metal chalcogenide compound - Liew, Josephine Ying Chyi; Talib, Zainal Abidin; Mat Yunus, Wan Mahmood; Zainal, Zulkarnain; Abd. Moksin, Mohd Maarof; Lim, Kean Pah; Wan Yusoff, Wan Mohamad Daud (American Institute of Physics, 2006)
This paper reports the preparation and the characterization of the (CuSe)1−xSex metal chalcogenide semiconductor compounds with different stoichiometric compositions of Se (x = 0, 0.2, 0.4, 0.5, 0.6, 0.8, 1.0) in bulk form. The (CuSe)1−xSex compounds were prepared using the solid state reaction by varying the ratio of CuSe:Se in the reaction mixture. X‐ray powder diffraction analysis is used to identify and measure the mass absorption coefficient of the (CuSe)1−xSex compounds to support the thermal diffusivity behaviour. The thermal diffusivity of the polycrystalline (CuSe)1−xSex compounds were measured and analyzed for the first time, using the photoflash technique. The thermal diffusivity values were determined to be in the range of 2.524 × 10−3 cm 2 /s to 1.125 × 10−2 cm 2 /s. It was found that the thermal diffusivity value tends to decrease as the parameter x increases. The relationship between the thermal diffusivity, mass absorption coefficient and density of the (CuSe)1−xSex are discussed in detail.